(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
In today’s world, we have seen substantial progress in the realm of Education, especially in the instruction of foreign languages. The communicative language teaching method has become a crucial part of English teaching techniques and is still widely used by language teachers. Furthermore, scholars are actively researching and examining the subject of communicative language teaching.